Digital Media: Algorithmic Amplification of Hate Speech and Its Impact on Social Cohesion in the Kurdistan Region - Hemin Amen Jalal Shwani; Tahir Haso Zebari (Zanco Journal of Human Sciences, 2026)
In providing insight into the impact of digital media on societal harmony, this research addresses the issue of Digital Media: Algorithmic Amplification of Hate Speech and Its Impact on Coexistence and Social Cohesion in the Kurdistan Region. The study aims to identify the role of algorithms in deepening polarization and threatening peaceful coexistence among different communities. Participants were recruited through non-probability sampling, comprising 488 digital media users across the region. The study employed a survey methodology, using an electronic scale with multiple items to measure “exposure to hate speech” and “belief in coexistence.” This method is useful for analyzing associations and predictive relationships, as well as for gaining a systematic understanding of factors influencing attitudes toward coexistence. Data were analyzed using statistical tools from the SPSS program, including correlation and multiple regression analysis. The most significant findings revealed a weak positive correlation between exposure to hate speech and belief in coexistence, indicating a “defensive reaction” phenomenon within society. Place of residence and ethnicity emerged as the most influential factors, while platform usage showed no statistically significant effect. These results suggest that digital media functions more as a mirror reflecting political and geographical realities than as a primary shaper of attitudes. Furthermore, although digital media can threaten social cohesion, it paradoxically strengthens the belief in “coexistence” a cornerstone of cohesion as a counter-response.